The Role of Education in Women Empowerment: A Survey Study in Kalikot District of Karnali Province (NPRC Journal of Multidisciplinary Research, 2025)
The present study aimed to examine the relationship between level of education and women empowerment conducted in Mahawai Rural Municipalty of Kalikot District and Birendra Nagar Municipality of Surkhet Districts belonging to the quantitative research design. Totally 700 educated married women between 20-45 years of age group from rural (N=350) and urban areas (N=350) were randomly selected. Structured questionnaire was used as a data collection tools. The study findings revealed that the urban women demonstrated higher representation across all levels of formal education compared to rural women. The mean educational level scores were 3.29 (SD=0.95) for rural, and 3.76 (SD=0.77) for urban women, respectively, with T-value of -2.65 (p